Neurotrophin-5: A novel neurotrophic factor that activates trk and trkB - Berkemeier, Lucy R.; Winslow, John W.; Kaplan, David R.; Nikolics, Karoly; Goeddel, David V.; Rosenthal, Arnon (Neuron (Cambridge, Mass.), 1991)
In vertebrates, the formation and maintenance of neuronal connections are subject to regulation by multiple target-derived, diffusible (neurotrophic) factors. Here we describe the identification and characterization of a novel neurotrophic factor designated neurotrophin-5 (NT-5). NT-5 is structurally related to nerve growth factor and is expressed in embryonic as well as adult tissues. Recombinant NT-5 promotes the survival of peripheral sensory and sympathetic neurons and induces differentiation of the pheochromocytoma cell line PC12. NT-5 activates two trk-related tyrosine kinase receptors and shares these receptors with other neurotrophins. Activation of multiple receptors may permit a single neurotrophin to control target innervation by distinct neuronal populations. Receptor sharing could enable neurotrophic factors emanating from distinct targets to cooperate in regulating neurons with multiple connections.